Research on piping in fine materials to be used in dams for water storage - Rosales, Erick (2025)
The present work evaluates the susceptibility to piping of soils used in the construction of earth dams based on laboratory tests, for which an experimental device has been developed based on the methods for evaluating erosion in cohesive soils developed by Wan & Fell and on standard methods for identifying dispersive. 28 soil samples grouped into 7 types (CH, sandy CL, CL, SC, ML, MH and SM) were evaluated from which the critical shear stress (τc) and the representative index of erosion rate (Ĩ) were determined. allows characterizing the behavior of the soils analyzed as extremely fast for the SM sample, very fast for the ML samples, moderately fast for the MH and CH samples and moderately slow for the CL, sandy CL and SC samples whose values ​​for the conditions carried out vary from 0.1588 to 0.6607 being this parameter dimensionless. The significant factors that influence piping are the maximum dry density obtained from the compaction tests, the percentage of silt and the plasticity index. Piping occurs in soils without cohesion (silty sand) or with low plasticity (with a plasticity index less than 6 percent) and in cohesive soils with a plasticity index greater than 15 percent and with a silt percentage greater than 40 percent, compacted with the maximum dry density and the optimum moisture content obtained from the compaction tests.